VACCINE SURGE MOMENT: A ONE-STOP SERVICE APPROACH TO ACHIEVING MAXIMUM PROTECTION THROUGH IMMUNIZATION: MOMEN SERBU VAKSIN: PENDEKATAN ONE-STOP SERVICEDALAM MEWUJUDKAN PERLINDUNGAN MAKSIMAL MELALUI IMUNISASI - Arshy Prodyanatasari; Putu Daneswara Widodo; Zahra Aulia Devita Sari; Dandi Setiawan; Sabrina Saskia Eka Nova; Rossita Rachmania (PT. ROCE WISDOM ACEH, 2026)
The high rate of incomplete basic immunisation among infants and toddlers is a serious public health issue, as it increases vulnerability to preventable diseases. This community service activity was motivated by the need for immediate intervention to catch up on missed immunisation coverage and to increase parents‟ understanding of vaccination‟s importance. This activity aims to increase parents‟ knowledge about immunisation and increase participation in the basic immunisation programme for infants and toddlers in Wates Village, Kediri District. The activity was carried out using the „Vaccine Blitz Moment‟ approach, which consists of three main stages: (1) Health education through pre-tests, education, and posttests to measure knowledge improvement; (2) Health screening using standard forms to ensure vaccine recipients‟ eligibility; and (3) Immunisation Administration according to the recommended schedule. The activity involved 16 infants and toddlers and their parents. There was a significant increase in parents‟ knowledge of 102.87% (from an average pre-test score of 47.81 to a post-test score of 96.99). A total of 16 children were successfully immunised, with the highest coverage for the Penta, Polio, PCV, and RV vaccines, as well as Measles and IPV. Multi-stakeholder collaboration and a comprehensive approach proved effective in increasing parental knowledge and immunisation coverage. This model can be adopted as a strategy to catch up on immunisation in other regions.